Prophet Sulayman and the Queen of Saba - Khan, Saniyasnain (Ajman,U.A.E Iqra book Distribution, 2024)
This delightful board book is a perfect gift for little children. The Quran story of Prophet Sulayman and the Queen of Saba, comes with beautiful illustrations and engaging text. The story has a moral in the end.
Keywords: Islamic Book